(untitled) (GEOgraphia, 2025)
The election of Jair Bolsonaro in Brazil in 2018 drew on an electoral coalition linking affluent urban neighborhoods, poorer urban peripheries, and agricultural districts, while failing to win the poorest rural regions. Analysis has tended to focus on the urban dimensions of this electoral geography. This paper addresses this omission by examining the case of a farming town in Rio Grande do Sul. Using qualitative data to explore how social and economic changes and challenges were understood and narrating, it argues a combination of historical and contemporary factors created conditions in which local citizens narrowly voted for Bolsonaro.